Simulasi Optimasi Reactive Distillation untuk Membuat Bioaditif (Triasetin) dari Gliserol dan Asam Asetat dengan Katalis Asam Sulfat Menggunakan Software Aspen Plus - Chici Wardiani Prasongko; Fitri Ramdani; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2018)
Biodiesel is one product to avoid the energy crisis in the front mass. Oil from plants such as oil palm, coconut, jatropha, or used cooking oil produces glycerol as a by-product of about 10 wt% of biodiesel products. The excess amount of glycerol must be converted into high-value products. Because if glycerol is not processed properly, the price of glycerol in the market will drop and it will become a waste that can pollute the environment. One of the derivatives of glycerol which has a high value is triacetin which is a good bio-additive as an anti-knock substance in vehicles. From this study, the synthesis of triacetin is from glycerol and acetic acid using sulfuric acid as a catalyst using the Reactive Distillation (RD) process. RD can be used as a reaction place and at the same time as a product refining place. RD can separate water with acetic acid as a distillate product for about 75% on the bottom product. The bottom product of RD will produce triacetin and other derivatives which will be separated again using the second column to obtain high purity triacetin. The purpose of this study is to simulate using Aspen Plus software to model the optimization of RD with a continuous system. The feed capacity of 96% glycerol was 4336.4550 kg/hour and 98% acetate acid was 8659.79 kg/hour in the liquid phase with the help of a sulfuric acid catalyst of 115.4592 kg/hour. The feed enters continuously into RD with a temperature of 115 Â°C and a pressure of 1 atm. The simulation results show that triacetin products can reach 99% as many as 10150.8561 kg/hour with glycerol conversion of 99.8% and 30 stages in RD. Besides that, the simulation results can also show the flow rate of each stage and the dimensions of RD.